HUBUNGAN ANTARA TIPE KEPRIBADIAN BIG FIVE DENGAN ADIKSI INTERNET PADA MAHASISWA DI SURABAYA - Tiek Budysan; Fransisca Febriana Sidjaja (Universitas Katolik Widya Mandala Surabaya, 2019)
Internet addiction is a phenomenon generally present among youngsters. One of the factors suggested to be the cause of internet addiction is personality. The present study aims to investigate the relationship between types of personality based on Big Five Theory (extraversion, agreeableness, conscientiousness, neuroticism, and openness) and internet addiction among university students in Surabaya. Within this study, 151 university students with internet addiction in Surabaya were recruited using purposive sampling method. Using the Kendall’s Tau b non-parametric correlation technique, the current study found that neuroticism is the only Big Five personality type that shows a significant relationship with internet addiction (r = 0,121, p=0,034; p